The role of preoperative lung rehabilitation training combined with nutritional intervention on surgical tolerance and accelerated recovery indicators in patients with moderate to severe COPD complicated with lung cancer - Hu, Yan; Cheng, Qin; Guo, Qiucheng (Frontiers in Surgery, 2025)
BackgroundLung cancer and chronic obstructive pulmonary disease (COPD) commonly coexist simultaneously and individuals with COPD are at a higher risk of developing lung cancer. Nutritional intervention has a restorative effect on COPD combined with lung cancer, but there is almost no research on lung rehabilitation training, and there are even fewer studies on the combination of the two.ObjectivesOur study aimed to assess the role of preoperative lung rehabilitation training plus nutritional intervention on surgical tolerance and accelerated recovery indicators in patients with moderate to severe COPD complicated with lung cancer.MethodsA total of 92 patients with COPD complicated by lung cancer who underwent surgery at our hospital between February 2023 and March 2024 were enrolled. Using a block randomization method, patients were divided into two groups: the control group (n = 47) receiving only nutritional intervention, and the observation group (n = 45) receiving a combination of lung rehabilitation training and nutritional intervention. The following indicators were compared between the two groups: pulmonary function parameters [forced expiratory volume in 1 s (FEV1), FEV1/forced vital capacity (FVC), maximum voluntary minute ventilation percentage (MVV%), and lung carbon monoxide diffusion capacity (DLCO)], Modified Medical Research Council (MMRC) dyspnea scale score, 6 min walking distance (6MWD), blood gas indicators [arterial partial pressure of oxygen (PaO2) and arterial partial pressure of carbon dioxide (PaCO2)], quality of life, and postoperative complication rate.ResultsAfter intervention, the observation group showed significantly higher levels of FEV1, FEV1/FVC, MVV%, DLCO, and 6MWD compared with the control group, while the MMRC score was significantly lower (all p < 0.05). Regarding blood gas indicators, the observation group had a significantly higher PaO2 level and a significantly lower PaCO2 level than the control group (p < 0.05). Additionally, the quality of life score in the observation group was significantly higher, and the postoperative complication rate was significantly lower than those in the control group (both p < 0.05).ConclusionPreoperative lung rehabilitation training combined with nutritional intervention can effectively improve pulmonary function and respiratory function in patients with moderate to severe COPD complicated by lung cancer, enhance their surgical tolerance, improve quality of life, and reduce the incidence of postoperative complications.